POLITICAL ORIENTATION OF IVAN MAZEPA IN ARTISTIC INTERPRETATION BY BOHDAN LEPKYI AND VOLODYMYR SOSIURA - Голобін, В. М.; Кісь, Я. І.; Макаровський, І. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with historical and politological analysis of Bohdan Lepskyi’s essays as well as Volodymyr Sosiura’s ones namely triology "Mazepa" and poem "Mazepa". Historical conditions of hetman Ivan Mazepa’s activities and his political orientation are cleared up.